Existence and Uniqueness of Solution to Nonlinear Boundary Value Problems with Sign-Changing Green’s Function - Peiguo Zhang; Lishan Liu; Yonghong Wu (Abstract and Applied Analysis)
By using the cone theory and the Banach contraction mapping principle, the existence and uniqueness results are established for nonlinear higher-order differential equation boundary value problems with sign-changing Green’s function. The theorems obtained are very general and complement previous known results.